Menggagas Pesantren Pluralis: Rekontruksi Sistem Pendidikan Pesantren dalam Bingkai Pluralisme - M. Muntabihun Nafis (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Pesantren, which in teaching is more emphasis on religion, making education pattern which tend to dichotomic impression. Pesantren should provide various opportunities for expanding the curriculum that intersect and are familiar with science and modern methodology. Important figures involved in the world of boarding schools also have to engage in dialogue for the practice of teaching culture is not too dogmatic. In addition, the interpretation does not claim any absolute truth, so that it can emancipatory. Such practices if realized will be come a binding system, and can release from the perception of dichotomic boarding education. Pesantren doing reconstruction on the pattern to burn into a system that aligned with the dynamics of contemporary society. Which this framework, expected learning the practice of pluralism in Islamic boarding schools can succeed. Keywords: Pluralism, Education, School, Reconstruction, and the System.